2013
DOI: 10.1017/s1431927613000731
|View full text |Cite
|
Sign up to set email alerts
|

On oral calcifications: sialoliths, dental calculi and tonsilloliths

Abstract: The oral cavity is susceptible to several calcifications such as salivary calculi (sialoliths), dental calculus (tartar) and tonsillar concretions (tonsilloliths). Although several individual studies had been already carried out, a comprehensive morphological and elemental comparison between them is still missing.Sialoliths are most commonly found in the submandibular glands and are composed of regions rich in Ca and P minerals, namely hydroxyapatite, whitlockite and brushite, and regions consisting of organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
5
0
1
Order By: Relevance
“…[10,11,12] However, not all biomineralization is desirable. In humans calcium oxalate is a biomineral with great medical significance, specifically regarding urolithiasis [13] and the formation of kidney stones. [14,15] This undesirable disease affects ~10% of the world's population per generation [16] with an expected increase in the number of carriers for the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11,12] However, not all biomineralization is desirable. In humans calcium oxalate is a biomineral with great medical significance, specifically regarding urolithiasis [13] and the formation of kidney stones. [14,15] This undesirable disease affects ~10% of the world's population per generation [16] with an expected increase in the number of carriers for the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…Biomineralization 4 (the ability of living organisms to mediate mineral formation) is a hugely important and widespread process that can be seen in everyday materials such as bone, 5 teeth, 5 skeletal tissues in sponges, 6 crustaceans, 7 egg shells 8 , mollusc shells 9 and calcium oxalate is a known biomineral that contributes to urolithiasis 10 . Calcium oxalate makes up approximately 70% of kidney stones while other components are calcium phosphate ~8.9%, uric acid ~10.1%, struvite ~9.3%, various organic materials ~0.8% and cystine ~0.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Another study using SEM and TEM analysis reported similar qualities of sialoliths and calculus, such as a layered structure and presence of crystals. This correlation could clarify the mineralization process in sialoliths 6 . However, in the current study, we did not find similarities between sialoliths, tonsillolilths and antroliths.…”
Section: Discussionmentioning
confidence: 73%
“…The submandibular gland is the most affected organ (85%) and parotid and sublingual glands are affected in 10% and 5% of cases, respectively 5 . Recent studies show that while sialoliths have complex structure, with a central core surrounded by concentric layers, calculus and tonsilloliths do not present distinctive architecture 6 . While some studies have been carried out, there are no comprehensive comparisons of morphology and composition of sialoliths, tonsilloliths, and antroliths.…”
Section: Introductionmentioning
confidence: 99%